Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025655
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Suit

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms ABSTRACTWe present the concept of Frozen Suit, a type of clothing that restricts users' movements at joint positions (e.g. elbow, knee) via a changeable stiffness jamming material. The suit can "freeze" users' body parts, for example during a game in order to provide the physical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The concept of material anisotropy for shape-change has been investigated to some extent by HCI researchers by using particle jamming to achieve variable stiffness properties, such as in [1,67], where the authors focused on alternating between soft and hard deformability. However, Ou et al [171] showed that it was also possible to introduce anisotropic deformation using jamming through the structural design of the jammable materials, such as by weaving multiple jamming units into the material, using interleaving flaps in the elastic air bladder, or by introducing crease patterns or cutting geometrical patterns into the jamming flaps [169].…”
Section: Anisotropic Structures Within Hcimentioning
confidence: 99%
“…The concept of material anisotropy for shape-change has been investigated to some extent by HCI researchers by using particle jamming to achieve variable stiffness properties, such as in [1,67], where the authors focused on alternating between soft and hard deformability. However, Ou et al [171] showed that it was also possible to introduce anisotropic deformation using jamming through the structural design of the jammable materials, such as by weaving multiple jamming units into the material, using interleaving flaps in the elastic air bladder, or by introducing crease patterns or cutting geometrical patterns into the jamming flaps [169].…”
Section: Anisotropic Structures Within Hcimentioning
confidence: 99%
“…prosthesis or the sixth finger device [71]) to enhance manipulation dexterity. Conversely, smart fabric can change its stiffness around the user's joints to restrict their movement in gaming, training, or rehabilitation [1].…”
Section: Augment Usersmentioning
confidence: 99%
“…A significant challenge remains in the availability of small form-factor, minimal weight, and high resolution actuators. In line with more general computing trends, shape-changing interfaces are moving from stationary to mobile to wearable form factors [1,46], and from rigid to flexible to stretchable and even floating shapes [27,57,62,65]. The use of electromechanical actuators, as is common in many systems (e.g.…”
Section: Miniaturized Device Form Factors and High Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used technology for wearable tactile interfaces, including commercial products, is vibro-tactile output. Other forms of actuations methods such as thermal [49,52,66], pneumatic [20,2], shear forces [23], ultrasound [68,55], wind flow [43] and brushing [58] have been demonstrated.…”
Section: Related Workmentioning
confidence: 99%